Broadcasting In The Inevitability Of Digital Media Technology - Sari, Yunita; Nur Sya’adah, Siti; Nur Amaliah, Siti (CV. Inara, 2024)
The main driver of this revolution was the discovery and development of digital technology. The discovery and development of digital technology. The essence of digi- tal technology is the process of converting all forms of information (text, sound, and graphics) encoded into a code containing the digits 0 and 1. This research is a qualitative research with a literature review approach. The data sources used are secondary data from various journals, books, news, videos and other texts relevant to this study. The results of the study found, digital technology opens up the possibility to produce higher quality media content, both in terms of